Revitalisasi Peran Unit Bimbingan Dan Konseling Dalam Mendorong Pengembangan Diri Santri Di Pesantren Ulumul Quran Sumedang - Tajiri, Hajir; Satriah, Lilis (Participative Journal: Jurnal Pengabdian Pada Masyarakat, 2023)
In the teenage phase of students, a number of problems often arise, this cannot be separated from changes within themselves and also the environmental factors that raise them. The aim of service is to increase the knowledge, understanding and abilities of Islamic boarding school supervisors and counselors in providing developmental guidance and counseling services based on Islamic teaching values to Islamic boarding school students by this community service chooses a service learning model, where those involved include: students taking courses in developmental counseling courses, lecturers in developmental counseling courses, school counseling guidance service units, supervisors and caregivers of students as well as students in Islamic boarding schools. The findings: there are still quite a lot of students whose moral intelligence is categorized as vulnerable/problematic, identified by their inner voice being less sharp so they are confused about distinguishing right from wrong, sensitivity to doing good things, less able to avoid wrongdoing, alternative abilities best behavior in situations of bad choices. Counseling training provided to madrasah and Islamic boarding school caregivers includes material on moral intelligence and good counseling methods through lectures, discussions and simulations. Simulations are also provided involving students who have also been equipped with counseling skills.